2006
DOI: 10.1111/j.1557-9263.2006.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of plucked feathers versus blood samples as DNA sources for molecular sexing

Abstract: ABSTRACT. Feathers are increasingly collected as a nondestructive source of DNA for avian genetic research. Although feather samples are not optimal in some important ways than more robust blood or tissue samples, feather sampling requires less training for field workers, results in shorter handling times for the organism, generates no hazardous wastes, and requires simpler storage procedures. Along with these largely positive attributes comes a set of challenges, particularly the relatively low copy number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 21 publications
8
68
2
1
Order By: Relevance
“…the primers may match one CHD gene slightly less well that the other. Harvey et al (2006) supported our result give evidence that feathers can provide sufficient DNA for molecular sexing reactions. This low cost, speed, and ease of collection, storage, and transport of feather samples are the major advantages (Duan & Fuerst 2001).…”
Section: Disscussionsupporting
confidence: 93%
“…the primers may match one CHD gene slightly less well that the other. Harvey et al (2006) supported our result give evidence that feathers can provide sufficient DNA for molecular sexing reactions. This low cost, speed, and ease of collection, storage, and transport of feather samples are the major advantages (Duan & Fuerst 2001).…”
Section: Disscussionsupporting
confidence: 93%
“…In our study, about 79% of DNA extracts were from feather samples (n ¼ 136) and we found that, as expected, shorter fragments yielded significantly higher PCR efficiencies (Table 2). This is not unexpected because feathers usually contain less DNA (see, for example, Bush et al, 2005) that is sometimes more degraded than in blood and tissue samples (Harvey et al, 2006). Another factor affecting the PCR efficiency is storage condition.…”
Section: Discussionmentioning
confidence: 99%
“…We chose blood over feathers, for example, because bird blood is a better tissue for obtaining high amounts of DNA; nucleated erythrocytes provide much more DNA compared to relatively low amounts of DNA recovered from feather samples (Harvey, Bonter, Stenzler, & Lovette, 2006). We chose blood over feathers, for example, because bird blood is a better tissue for obtaining high amounts of DNA; nucleated erythrocytes provide much more DNA compared to relatively low amounts of DNA recovered from feather samples (Harvey, Bonter, Stenzler, & Lovette, 2006).…”
Section: Sample Collectionmentioning
confidence: 99%